Toward a feminist ethics of nonviolence - Cavarero, Adriana; Butler, Judith, 1956-; Honig, Bonnie; Guaraldo, Olivia; Battersby, Christine, 1946-; Bernini, Lorenzo, 1973-; Devenney, Mark, 1968-; Forti, Simona; Woodford, Clare; Huzar, Timothy J. (New York : Fordham University Press, 2021)
"Toward a Feminist Ethics of Nonviolence brings together three major feminist thinkers to discuss Cavarero's call for a postural ethics of nonviolence. The book consists of three longer essays by Cavarero, Judith Butler, and Bonnie Honig, followed by shorter responses by a range of scholars that widen the dialogue, drawing on post-Marxism, Italian feminism, and queer theory. Together, the authors contest the boundaries of their common project for a pluralistic, heterogeneous, but urgently feminist ethics of nonviolence."--Back cover.
Prelude / Timothy J. Huzar -- Introduction: Adriana Cavarero, feminisms, and an ethics of nonviolence / Timothy J. Huzar and Clare Woodford -- Scenes of inclination / Adriana Cavarero -- Leaning out, caught in the fall: interdependency and ethics in Cavarero / Judith Butler -- How to do things with inclination: Antigones, with Cavarero / Bonnie Honig -- Scherzo. Thinking materialistically with Locke, Lonzi, and Cavarero / Olivia Guaraldo -- Études. Cavarero, Kant, and the arcs of friendship / Christine Battersby -- Bad inclinations: Cavarero, Queer theories, and the drive / Lorenzo Bernini -- Querying Cavarero's rectitude / Mark Devenney -- From horrorism to the gray zone / Simona Forti -- Violence, vulnerability, ontology: insurrectionary humanism in Cavarero and Butler / Timothy J. Huzar -- Queer Madonnas: in love and friendship / Clare Woodford -- Coda / Adriana Cavarero.
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Nonviolence -- Moral and ethical aspects; Feminist ethics; Non-violence -- Aspect moral; Éthique féministe.; SOCIAL SCIENCE -- Gender Studies; Feminist ethics; Nonviolence -- Moral and ethical aspects; Adriana Cavarero; Bonnie Honig; Feminism; Judith Butler; ethics; gender; maternity; nonviolence; sex; the body